The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/850149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic deletion of Autotaxin from CD11b+ cells decreases the severity of experimental autoimmune encephalomyelitis

Abstract: AbstractAutotaxin (ATX) is a secreted lysophospholipase D catalyzing the extracellular production of lysophosphatidic acid (LPA), a growth factor-like signaling lysophospholipid. ATX and LPA signaling have been incriminated in the pathogenesis of different chronic inflammatory diseases and various types of cancer. In this report, deregulated ATX and LPA levels were detected in the spinal cord and plasma of mice during the development of experimental autoimmune encephalomyelitis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Here, we show that a robust ATX signal co-localizes with GFAP + cells in spinal cord sections of relapsing as well as remitting EAE. As shown in Figure 1A, increased ATX expression was observed during EAE, peaking at the remission phase as previously reported [18]. Intense ATX staining was detected in astrocytes at the peak of the disease (GFAP + cells; Fig.…”
Section: Increased Atx Staining In Spinal Cord Gfap + Cells During Eaesupporting
confidence: 86%
See 3 more Smart Citations
“…Here, we show that a robust ATX signal co-localizes with GFAP + cells in spinal cord sections of relapsing as well as remitting EAE. As shown in Figure 1A, increased ATX expression was observed during EAE, peaking at the remission phase as previously reported [18]. Intense ATX staining was detected in astrocytes at the peak of the disease (GFAP + cells; Fig.…”
Section: Increased Atx Staining In Spinal Cord Gfap + Cells During Eaesupporting
confidence: 86%
“…Increased ATX levels have been reported in the spinal cords of mice developing EAE; some of this ATX increase was attributed to activated CD11b + cell expression, mostly macrophages and microglia [18]. Here, we show that a robust ATX signal co-localizes with GFAP + cells in spinal cord sections of relapsing as well as remitting EAE.…”
Section: Increased Atx Staining In Spinal Cord Gfap + Cells During Eaesupporting
confidence: 68%
See 2 more Smart Citations
“…scRNAseq analysis of BALF cells from COVID-19 patients, where macrophages predominate, indicated that ENPP2 mRNA expression was detected in different macrophage subpopulations (Fig. 4C/UMAP, S3C/UMAP), where it could modulate their maturation in an autocrine mode via LPA (70)(71)(72). LPA has been also suggested to stimulate, in vitro, the conversion of monocytes to DCs (41,73,74).…”
Section: Discussionmentioning
confidence: 99%